A Further Comprehensive Review on the Phytoconstituents from the Genus Erythrina (Bangladesh Pharmaceutical Journal, 2020)
Erythrina is a significant source of phytoconstituents. The aim of this review is to solicitude of classification, synthesis, and phytochemicals with biological activities of Erythrina. In our previous review on this genus (Hussain et. al., 2016a) fifteen species (Erythrina addisoniae, E. caribeae, E. indica, E. lattisima, E. melanacantha, E. mildbraedii, E. poeppigiama, E. stricta, E. subumbrans, E. veriagata, E. vespertilio, E. velutina, E. zeberi, E. zeyheri and E. americana) have been studied and 155 molecules with chemical structures were reported. A further comprehensive review was done upon continuation on the same genus and thirteen species (E. abyssinica, E. arborescens, E. berteroana, E. burttii, E. caffra, E. coralloids, E. crista-galli, E. fusca, E. herbaceae, E. lysistemon, E. mulungu, E. speciosa and E. tahitensis) of Erythrina have been studied and 127 compounds are reported as phytoconstituents with their chemical structure in this review. Erythrina crista-galli and E. lysistemon consist of highest number of chemical constituents.Bangladesh Pharmaceutical Journal 23(1): 65-77, 2020